Search for H -> bb in association with a tt pair in proton-proton collisions at vs = 14 TeV - Schmidt, Alexander (KIT Scientific Publishing, 2007)
The main topic of this book is the determination of the potential to discover the Higgs boson at the Compact Muon Solenoid (CMS) experiment at the LHC in a certain decay channel. The production mode under investigation is the associated production with top quarks and the subsequent decay into b-quarks. The search for the decay into b-quarks is of special interest, because it has the highest branching ratio in the mass region shortly above the exclusion limit of 114.4 GeV. In addition, this channel facilitates measurements of Higgs coupling properties.